Studi Empiris Tentang Pengaruh Kualitas Produk, Brand Trust, dan Citra Merek terhadap Keputusan Pembelian Air Mineral Aqua - Tia Chisca Anggraeni; Ayu Kartika; Faramita Dwitama (BADAN PENERBIT STIEPARI PRESS, 2025)
This study analyzes the influence of product quality, brand trust, and brand image on purchasing decisions for Aqua bottled water in Tangerang Regency. This study uses a quantitative approach by conducting a survey of 100 respondents collected through a Google Form questionnaire. The tests carried out are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear analysis test, f test, t test and coefficient of determination test. The data used in this study used a Google form questionnaire and valid data that was successfully collected as many as 100 respondents. The testing tool used was IBM SPSS Statistics 23. The results of this study indicate that product quality, brand trust and brand image have a significant effect partially and simultaneously on purchasing decisions for Aqua bottled water in Tangerang Regency.